City with a Billion Dollar View - Cooper, G.C.K.; Namit, K. (Taylor and Francis, 2021)
The growth and intensification of many urban areas has meant city governments increasingly face pressure to limit development to preserve iconic city views. This is frequently achieved through ‘viewshafts’ or ‘sight lines’ that regulate development height across vast urban landscapes. While prevalent in many planning rule books, these policies are rarely subjected to rigorous economic appraisal, despite the large costs they can impose on local areas. We use a regression discontinuity to evaluate one such policy in Auckland, New Zealand which bifurcates the central business district (CBD). We find that the net cost of the policy to the local area is NZ$1.366 billion, or 16% of private land value in the CBD. At the margin, the constraint reduces land values by 40%. While removing these policies is not always easy or necessarily desirable, there may be value in optimization. One theoretical viewshaft alignment could reduce the net cost by 43%.